Pemanfaatan Kayu Eboni Untuk Penguatan Ekonomi Lokal Melalui Usaha Mikro di Mantikulore - Umar, Rukhayati; Mimpia, Kartini (Badan Riset dan Inovasi Daerah Sulawesi Tengah, 2025)
Ebony (Diospyros celebica) is a typical forestry commodity of Central Sulawesi, possessing both high economic and aesthetic value. However, its utilization at the local level is still limited and has not had a significant impact on improving the community's economy. This study aims to analyze the potential of ebony utilization in strengthening the local economy through the development of micro-enterprises in Mantikulore District, Palu City. The research method used is descriptive qualitative with data collection techniques through interviews, field observations, and review of supporting documents. The results show that ebony-based micro-enterprises have significant potential for development, especially in the high-value crafts and furniture sector. The main challenges faced include limited raw materials, strict regulations regarding protected wood status, and low managerial capacity of business actors. Recommended strengthening strategies include the establishment of ebony business centers, improving entrepreneurial skills, and strengthening partnerships between the community, local government, and research institutions to encourage sustainable local economic development.